A note on post-fire vegetation in pine forests of the Mordovia State Nature Reserve, Russia - Khapugin, Anatoliy A.; Ruchin, Alexander B. (Nature Conservation Research: Заповедная наука, 2025)
Wildfires pose dramatic and devastating effects on natural habitats around the world, being important determinants of environmental transformation. At present, pyrogenic successional patterns and forest structure remains quite unknown in damaged ecosystems. This paper was aimed to evaluate the plant abundance in pine (Pinus sylvestris) forests at various burning treatments in the Mordovia State Nature Reserve, European Russia. In 2021–2023, the sampling was performed on 11 permanent plots, including two unburned, three once-burned (in 2010 only), and six twice-burned (in 2010 and 2021) sites. On 11 plots, 36 vascular plant species from 32 genera and 21 families have been registered in total. Expectedly, the results demonstrated significant (p < 0.05) differences between once- and twice-burned plots based on the plant abundance in both ground and shrub-sapling layers, which can also be explained by differences in the time of the post-fire regeneration of the forest ecosystem. Based on plant abundance in the ground layer of burned sites, significant (χ2 = 11.880, p < 0.01) differences were found between the studied years. Significant differences in plant abundance on burned plots were found between 2021 and 2023 (p < 0.01), and 2022 and 2023 (p < 0.05). At the same time, no differences (χ2 = 3.816, p = 0.148) were found between the studied years based on plant abundance in the shrub-sapling layer on burned plots. The obtained results confirm the main patterns of post-fire re-vegetation in forest communities, but require additional studies to make stronger conclusions.